Area measurement: structuring with nonsquare units. Issue 2 (2nd April 2020) - Cullen, Amanda L.; Barrett, Jeffrey E.
ABSTRACT: In this article, we describe how students structured 2-dimensional space with square and nonsquare units. We employed a cross-sectional design, interviewing 5 students from each of 4 different grade groups: Grades 1, 3, 5, and 7 (ages 7, 9, 11, and 13) in structured, task-based interviews. Our findings about students' ways of measuring area fit a hypothetical route of learning, validating 4 specific levels of thinking about area units across tasks, regardless of unit shape and dimension indicators. Implications for instruction and research are discussed.